Relay Tuning of PID Controllers For Unstable MIMO Processes - Chidambaram, M. (Advances in Industrial Control,, 2018)
This book presents comprehensive information on the relay auto-tuning method for unstable systems in process control industries, and introduces a new, refined Ziegler-Nichols method for designing controllers for unstable systems. The relay auto-tuning method is intended to assist graduate students in chemical, electrical, electronics and instrumentation engineering who are engaged in advanced process control. The book's main focus is on developing a controller tuning method for scalar and multivariable systems, particularly for unstable processes. It proposes a much simpler technique, avoiding the shortcomings of the popular relay-tuning method. The effects of higher-order harmonics are incorporated, owing to the shape of output waveforms. In turn, the book demonstrates the applicability and effectiveness of the Ziegler-Nichols method through simulations on a number of linear and non-linear unstable systems, confirming that it delivers better performance and robust stability in the presence of uncertainty. The proposed method can also be easily implemented across industries with the help of various auto-tuners available on the market. Offering a professional and modern perspective on profitably and efficiently automating controller tuning, the book will be of interest to graduate students, researchers, and industry professionals alike.